Quality control of instruments for measuring the characteristics of bactericidal UV radiation - O. A. Minaeva; A. V. Ragutkin; S. I. Anevsky; R. V. Minaev; Th. T. Minh; I. A. Romanova (Российский технологический журнал, 2024)
Objectives. Quality control of instruments for measuring bactericidal irradiance of ultraviolet (UV) radiation is based on studying the main metrological characteristics. These characteristics include: angular and spectral sensitivity; linearity range; and absolute calibration in irradiance units. Deviations of the angular sensitivity of measuring instruments from the ideal cosine characteristic can significantly impact error estimation. They can also lead to the distortion of measurement results and a significant difference in instrument readings. The aim of this work is to enhance accuracy in resolving metrological problems of determining irradiance of bactericidal radiation.Methods. An effective method of resolving this problem is to introduce correction coefficients for the angular sensitivity of radiometers, spectroradiometers and dosimeters. The values are calculated based on the results of measurements on the goniometer when testing measuring instruments. An important role is played by computer models and digital twins of measuring instruments based on the results of studies of the metrological characteristics of radiometers by means of software. This includes modeling the measuring task.Results. The study of angular dependence of bactericidal UV radiometer sensitivity complemented by an analysis of measurement results obtained by other authors allows determining the value of the angular sensitivity correction coefficients by the deviation of the angular sensitivity of the irradiance measuring instruments of bactericidal radiation from the standard cosine dependence.Conclusions. Deviations of the angular dependence of bactericidal radiation UV radiometer sensitivity from the cosine characteristic lead to a significant underestimation of the irradiance measurements results from extended emitters. An effective solution is the use of digital angular sensitivity correction coefficients to measure the irradiance of bactericidal radiation determined during tests. When assessing the quality of radiometers, spectroradiometers and dosimeters for bactericidal radiation, incomplete control of the main metrological characteristics of the measuring instruments creates risks of serious errors in the measurement results of bactericidal irradiance.